Development trends of diversified agro-industrial enterprises in the context of international integration of economic relations - V. Prokhorova, Viktoriya (2020)
Globalization and growing competition have exacerbated the problems of analysis and diagnosing the level of economic development sustainability and the possibilities of economic entity market potential use at the global level. The development of a complete, reliable and up-to-date information base on the current financial, economic and technical level of an industrial enterprise development, its strategic development opportunities, making informed effective decisions on the directions of diversification or agro-industrial production restructuring is extremely important today from the standpoint of state policy development regarding the support for the key sectors of the Russian agro-industrial complex.In modern conditions, characterized by the intensification of economic relation integration in international markets,